2018
DOI: 10.1002/jum.14574
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Evaluation of Echocardiograms to Establish Normative Inferior Vena Cava and Aortic Measurements for Children Younger Than 6 Years

Abstract: In children younger than 6 years, the IVC and aorta increase linearly as the children grow. Such normal curves will be beneficial for assessing a pediatric patient's hydration status or right heart function in patients with congenital heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In contrast, the impact on IVCmax/Ao was weak in both children and adults (R 2 =0.039, R 2 =0.005 for female and male children, R 2 =0.123 for Ao in adults). Similarly to our study, Stenson et al (21) investigated the normative of IVC and Ao measurements in children younger than 6 years and found that both IVC and aortic dimensions increased in a linear fashion and had excellent correlations with the body surface area, body mass, and height. Our study first found that IVCmax/Ao is not susceptible to individual patient characteristics in children aged 1 to 13, though IVCmax and Ao are susceptible to individual patient characteristics.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, the impact on IVCmax/Ao was weak in both children and adults (R 2 =0.039, R 2 =0.005 for female and male children, R 2 =0.123 for Ao in adults). Similarly to our study, Stenson et al (21) investigated the normative of IVC and Ao measurements in children younger than 6 years and found that both IVC and aortic dimensions increased in a linear fashion and had excellent correlations with the body surface area, body mass, and height. Our study first found that IVCmax/Ao is not susceptible to individual patient characteristics in children aged 1 to 13, though IVCmax and Ao are susceptible to individual patient characteristics.…”
Section: Discussionsupporting
confidence: 84%
“…Ultrasonography of the CVC visualized between the 9th and the 12th intercostal space in HF calves demonstrated that the circumference of the CVC increases with age [ 21 ]. Studies performed on healthy children also showed a positive correlation between age and IVC and Ao diameter, and, inconsistently, with the IVC and Ao index [ 25 , 26 , 27 , 28 ]. Del Prete et al (2021) showed a correlation between age and the long axis of CVC and the CVC and Ao diameter index [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The third limitation: if IVC/aorta ratio measurement could have been done to our participants, which would have contributed to the literature in terms of normative values. Because, in a previous study, 0.8 value was reported as normal for normative values for IVC-DI/aorta in euvolemic children under 3 years of age [24]. Originally, in the planning phase of the study, we did plan to determine the IVC-DI normative values.…”
Section: Discussionmentioning
confidence: 99%